The impact of social media peer communication on customer behaviour – evidence from Romania - Anastasiei, Bogdan; Dospinescu, Nicoleta; Dospinescu, Octavian (Publishing House of Wroclaw University of Economics and Business, 2022)
This paper investigates the effects of the type of appeal (emotional vs. rational) on the persuasiveness of social media messages related to products, services and brands. Previous research shows that electronic word-of-mouth spread through social media has a strong influence on customers’ purchase decisions. This paper examines whether this influence depends on the type of appeal used in the message. The research method was based on a survey administered online to a sample of 369 students. The survey questionnaire contained 21 closed questions. The message credibility itself is slightly influenced by the type of appeal (rational or emotional): rational messages are more convincing than emotional ones. On the other hand, the type of appeal strongly influences both purchase intention and perceived purchase risk. While the perceived risk is lower for the rational messages, the intention to buy the product is higher for the emotional messages, due to the particular characteristics of the studied product (smartphone).The findings have practical importance for companies that promote their products through social media. They should use both the emotional and rational approach in their messages: the emotional posts use feelings to make customers buy, while the factual messages help customers reduce the perceived risk of making a wrong decision. The paper contributes to a more advanced understanding of how rational and emotional posts in the social media impact on the customer’s behaviour.
Argumenta Oeconomica, 2022, Nr 1 (48), s. 247-264
Keywords: social media; word of mouth; emotional appeal; rational appeal; propensity to buy